A stable isotopic constraint on the origin of sulphur ore excavated from the exotic four‐lobe jars that prevailed during late medieval to early modern times in Sakai (Osaka), south‐western Japan. (6th May 2014) - Mizota, C.; Yamanaka, T.
Abstract : Stable sulphur isotope ratios were determined for native sulphur ore that was excavated from exotic four‐lobe jars in Sakai, south‐western Japan. The jars were buried after a fire event that occurred on 28 April 1615. The sulphur isotopic results (average δ 34 S = +0.5‰) were evaluated in terms of comparing ancient documents with a database from new sulphur collections. The origin of the sulphur ore is estimated to be transportation from native sulphur deposits formed around the solfataric fumaroles from Mts Garan and Kuju–Iwozan, in central‐eastern Kyushu. These analytical results support the validity of history based on the analysis of ancient documents.